Attitude of senior pupils to the values of physical culture - Саінчук, М. М. (Slobozhanskyi Herald of Science and Sport, 2011)
A study to determine the terminal nucleus (vitally meaningful) values of high school students on how to Rokicha M. It was found experimentally that the modern high school among the many values, goals and motives for attending physical education chooses exactly health. Displaying the actual actions taken in this age category on healthy lifestyles and on this basis, it is assumed that most students simply declare health as a primary value for them.